DIAGNOSTICO PARA LA IMPLEMENTACIÓN DE UN PARQUE ACUÁTICO EN LA RUTA DEL RIO-CANTÓN QUEVEDO PROVINCIA LOS RÍOS. - Vera Muñoz, Daily Stefanny (2022)
Currently, Quevedo is considered one of the most prosperous cities at the provincial level, presenting one of the greatest growths in the economic and productive sphere compared to other cantons of the provinces, at the national level they are ranked as the third canton whose tax collection grew by a rate of 2.6% per year below Duran and San Jacinto de Yaguachi. The purpose of the research is to carry out the diagnosis for the implementation of a water park on the route of the river-canton Quevedo, Los Ríos Province, for which a survey was applied to 80 people who visited the river route on a weekend. It was determined that 81% of the respondents agree that a water park be implemented in the city of Quevedo, in addition 50% of them stated that they would visit the water park at least once a week in hot weather. 25% of those surveyed indicate that there should be swimming pools for adults and children, with slides included; and that both typical food and fast food restaurants are elementary. 94$ are willing to pay up to 3 dollars for admission and 63% would spend between 30 and 40 dollars per visit to the water park. It is concluded through this diagnosis that this amusement center called water park should be implemented and it is recommended to carry out training programs for the personnel that would attend it, as well as to ensure the safety of the premises and the tourists